Effectiveness of Transcranial Direct Current Stimulation and Monoclonal Antibodies Acting on the CGRP as a Combined Treatment for Migraine (TACTIC): Protocol for a Randomized, Double-Blind, Sham-Controlled Trial - Ornello, Raffaele; Rosignoli, Chiara; Caponnetto, Valeria; Pistoia, Francesca; Ferrara, Michele; D'Atri, Aurora; Sacco, Simona (Frontiers in Neurology, 2022)
Background Migraine is a recurrent headache disorder that has a still unclear pathophysiology, involving several circuits of both the central and peripheral nervous system. Monoclonal antibodies acting on the calcitonin gene-related (CGRP) pathway (CGRP-MAbs) are the first drugs specifically designed for migraine; those drugs act peripherally on the trigeminal ganglion without entering the blood-brain barrier. Conversely, neuromodulation techniques such as transcranial direct current stimulation (tDCS) act centrally by increasing or decreasing the neuronal firing rate of brain cortical areas. The aim of the study will be to evaluate whether tDCS, in addition to CGRP-MAbs, is an effective add-on treatment in reducing headache frequency, intensity and acute medication use in patients with migraine. To demonstrate the biological effects of tDCS, the electroencephalographic (EEG) power changes after tDCS will be assessed. Methods We will include patients with migraine on treatment with CGRP-MAbs and reporting ≥8 monthly migraine days. During a prospective 28-day baseline period, patients will fill in a headache diary and questionnaires to evaluate migraine-related disability, anxiety and depressive symptoms, sleep quality, and health-related quality of life. Subjects will be randomly assigned in a 1:1 ratio to active or sham tDCS. The stimulation protocol will consist in five daily sessions, the cathodes will be applied bilaterally above the occipital areas, with the reference anode electrodes positioned above the primary motor areas. Before the first, and immediately after the last stimulation session, patients will perform a 10-min resting EEG recording. During a 28-day follow-up period following tDCS, patients will have to fill in a headache diary and questionnaires identical to those of the baseline period. Discussion This trial will evaluate the efficacy of an add-on treatment acting on the brain in patients with migraine, who are already treated with peripherally acting drugs, showing how tDCS acts in restoring the dysfunctional brain networks typical of the migraine patient. Clinical Trial Registration NCT05161871.